Potential role of APOE ɛ4 allele as a modifier for the association of BDNF Val66Met polymorphisms and cognitive impairment in community-dwelling older adults - Ji, Shaozhen; Kang, Jia; Han, Chao; Xu, Xitong; Chen, Meijie; Chen, Jie; Chhetri, Jagadish K; Pan, Jing; Chan, Piu (Frontiers in Aging Neuroscience, 2024)
To determinate whether brain-derived neurotrophic factor (BDNF) Val66Met polymorphism is associated with cognitive impairment (CI) in the communitydwelling Chinese aged adults, and investigate whether this relationship is modified by Apolipoprotein E (APOE) ɛ4 allele.The study is a second analysis for 703 participants aged ≥60 years randomly enrolled from the Beijing Longitudinal Study of Aging II prospective cohort. Educationadjusted Mini-Mental State Examination and the Clinical Dementia Rating Scale measure cognitive performance of the subjects. Main effects and interactions (additive, multiplicative) of BDNF Met allele and APOE ε4 allele for CI were estimated by logistic regression models. Results 84 out of 703 older adults aged ≥60 years old were CI. No significant difference was observed in CI risk of participants with BDNF Met allele and that of subjects without BDNF Met allele (P = 0.213; P = 0.164). The individuals carrying both BDNF Met allele and APOE ε4 showed an almost 1.5-fold higher Odds for CI compared carriers of BDNF Met allele not APOE ε4. The additive association indicated a positive interaction of both BNDF Met and APOE ε4 alleles with broad CIs (P = 0.021; P = 0.018).The results suggested that APOE ε4 allele might be a potential modifier for the association of BDNF Val66Met polymorphism and CI among community dwelling older adults.